Overview of the library management system at SMA Negeri 1 Parongpong - Nabil Shubhi Syah Putra (Hipkin Journal of Educational Research, 2026)
Digital integration in library management, book collection development, user access, and strategies to increase student interest in reading are an important part of school libraries. This study aims to examine the role of the library management system in supporting the learning process at SMAN 1 Parongpong. This study uses a qualitative descriptive approach, with data collected through interviews with library managers. The results of the study indicate that the implemented digital library management system has facilitated the management of book borrowing and returns and helped adjust the collection based on students' learning needs. Although the system is not yet accessible online, its implementation has improved efficiency and expanded access to learning resources. The library also runs literacy programs, such as reading corners, and encourages student involvement in collection selection. However, challenges such as limited human resources and insufficient supervision of the collection remain obstacles that need to be addressed. Overall, this study confirms that digitally integrated library management has a significant contribution in supporting the learning process and strengthening literacy culture in the secondary school environment.   Abstrak Integrasi digital dalam pengelolaan perpustakaan, pengembangan koleksi buku, akses pengguna, serta strategi peningkatan minat baca murid merupakan hal yang penting bagi perpustakaan sekolah. Penelitian ini bertujuan untuk mengkaji peran sistem manajemen perpustakaan dalam mendukung proses pembelajaran di SMAN 1 Parongpong. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara bersama pengelola perpustakaan. Hasil penelitian menunjukkan bahwa sistem manajemen perpustakaan digital yang diterapkan telah mempermudah pengelolaan peminjaman dan pengembalian buku serta membantu dalam penyesuaian koleksi berdasarkan kebutuhan pembelajaran murid. Walaupun sistem tersebut belum dapat diakses secara daring, penerapannya telah meningkatkan efisiensi dan memperluas akses terhadap sumber belajar. Perpustakaan juga menjalankan program literasi seperti pojok baca dan pelibatan murid dalam pemilihan koleksi. Namun demikian, tantangan seperti keterbatasan sumber daya manusia dan kurangnya pengawasan terhadap koleksi masih menjadi hambatan yang perlu dibenahi. Secara keseluruhan, penelitian ini menegaskan bahwa pengelolaan perpustakaan yang terintegrasi secara digital memiliki kontribusi signifikan dalam mendukung proses pembelajaran dan penguatan budaya literasi di lingkungan sekolah menengah. Kata Kunci: digitalisasi dalam pendidikan; perpustakaan sekolah; sistem manajemen perpustakaan